Can fuzzy extension of Delphi–analytical hierarchy process improve hospital site selection?. (1st January 2014) - Chatterjee, Debmallya
Applications of Analytical Hierarchy Process (AHP) and its Fuzzy Extension (FAHP) can be witnessed in different Multi–criteria Decision–Making (MCDM) situations including location selection. However, the use of such a prominent MCDM tool is limited when it comes to hospital site selection in India. This paper makes an attempt to do a formal study of hospital site selection in India using AHP and its fuzzy extension. The study embeds Delphi both with AHP and FAHP in generating consensus and does a comparative analysis to verify the supremacy of one over another. Three rural locations from India are considered for a potential hospital in the study. Results indicate 'cost of land' as the most important sub–factor across both the integrated models followed by 'population characteristics'. D–AHP and D–FAHP has resulted in varying weights for few sub–factors nevertheless the differences are not statistically significant.